A systematic review of the effect of piston diameter in stapes surgery for otosclerosis on hearing results. (24th June 2015) - Wegner, Inge; Verhagen, Jessica J.; Stegeman, Inge; Vincent, Robert; Grolman, Wilko
Abstract : Objective: To evaluate the effect of piston diameter in primary stapedotomy for otosclerosis patients measured by hearing outcome. Data Sources: PubMed, Embase, and the Cochrane Library. Review Methods: A systematic search was conducted. Studies reporting original data on the effect of piston diameter on pure‐tone audiometric results in patients undergoing primary stapedotomy for otosclerosis were included. Relevance and risk of bias of the selected articles were assessed. Studies with low relevance, high risk of bias, or both were excluded. Absolute risks and risk differences, means and mean differences, and 95% confidence intervals were extracted. Results: Twelve studies with moderate to high relevance and moderate risk of bias were included for data extraction. Air‐bone gap closure to 10 dB or less was assessed in six studies, the majority of which did not show a statistically significant or clinically relevant difference between two pistons with a different diameter. More importantly, the differences that were found were not consistently in favor of smaller‐diameter pistons or larger‐diameter pistons. Mean postoperative air‐bone gap ranged from 3 dB in favor of a smaller‐diameter piston to 3 dB in favor of a larger‐diameter piston across four studies. Permanent sensorineural hearing loss was assessed in eight studies and occurred in only one study. In this study, no difference was found between a 0.4‐mm‐diameter piston and a 0.6‐mm‐diameter piston. Conclusion: There is not sufficient evidence to support the superiority of the use of a larger‐diameter piston compared to a smaller‐diameter piston for primary stapedotomy in otosclerosis patients. Level of Evidence: NA Laryngoscope, 126:182–190, 2016